2017
DOI: 10.1155/2017/8680714
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication Pattern among Social Science University Students in Northwest Ethiopia

Abstract: Background. Inappropriate self-medication causes wastage of resources among others. Method. This survey study was conducted to determine self-medication pattern of 404 social science university students in Northwest Ethiopia, who were selected through stratified random sampling technique. Data were collected using self-administered questionnaire and analyzed with SPSS version 20 statistical software. Binary Logistic Regression analysis was employed with P value < 0.05 considered statistically significant. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
3
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 21 publications
7
49
3
6
Order By: Relevance
“…Our cross sectional survey revealed that malaria, typhoid, stomach pains, diarrhea, and dysentery were the most common illnesses for which self-medicated antibiotics were used amongst undergraduate students and community members. Among social science university students in Northwest Ethiopia, it was observed that headache was the common symptom for indiscriminate use of antimicrobials [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Our cross sectional survey revealed that malaria, typhoid, stomach pains, diarrhea, and dysentery were the most common illnesses for which self-medicated antibiotics were used amongst undergraduate students and community members. Among social science university students in Northwest Ethiopia, it was observed that headache was the common symptom for indiscriminate use of antimicrobials [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Using SPSS version 20, mean, standard deviation, standard error of the mean was calculated for each parameter in the different groups [28]. Continuous variables between groups were compared by independent t-tests or analyses of covariance as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In the present meta-analysis, six Ethiopian Universities were represented. Four of the studies were from Amhara [29,27,30,31], three from Oromia [28,32,34], and two from Tigray [25,33]. Regarding the response rate, almost all studies had a response rate of greater than 90%, and one studies did not state the response rate [27].…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Regarding the response rate, almost all studies had a response rate of greater than 90%, and one studies did not state the response rate [27]. Among included studies Six of them used stratified sampling technique [27,31,28,25,33,31,30] two of them used simple random sampling [32,29], and one used convenient sampling techniques [34] (Table 1).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation